Scanning Electron Microscopy of Goniodes dissimilis Denny, 1842 (Insecta: Phthiraptera) from Domestic Chickens on Seram Island - Maria Nindatu; Rony Marsyal Kunda; Mery Pattipeilohy; Yofian Anaktototy; Ventia Cika Tanikwele; Adriana Hakapaa (Postgraduate, University of Mataram, 2026)
Goniodes dissimilis (Denny, 1842) is one of the chewing lice (Ischnocera: Phthiraptera) that commonly infests native chickens (Gallus gallus domesticus). The aims of this study were to describe the morphological and ultrastructural characteristics of G. dissimilis using scanning electron microscopy (SEM). The sampling of Goniodes dissimilis was conducted in Seruawan, Hatusua, and Kamarian villages on Seram Island. SEM preparation was carried out through 2.5% glutaraldehyde fixation, 0.25 M phosphate buffer post-fixation, multistage dehydration, critical-point drying, mounting on stubs, and gold coating before being observed at various magnifications. SEM results showed that G. dissimilis from Seram Island has ultrastructural characteristics, such as the head is circumfasciate with a rounded anterior margin, a complete band on the marginal carina, a pulvinus surrounding the ventral carina, and no hyaline margin. The eyes appear reduced with long ocular setae, while the temporal region has five marginal setae, with setae numbered 2 and 3 presents. The antennae are sexually dimorphic, consisting of a scape, pedicle, and three flagellomeres. In this study, we collected only females of G. dissimilis, and the first flagellomer shows no radial grooves in the sensilla placodea. The thorax shows a pteronotum with several long spines, while the abdomen shows medially separated tergums II–VIII, spiracles on tergums III and VIII, and a thin, membranous sternal plate. The SEM results also show that the female G. dissimilis has terminalia displaying a dorsal plate connected with tergopleurites and a vulva lined with fine setae. This finding represents the first ultrastructural record of the G. dissimilis population on Seram Island, thereby enriching the morphological diversity and distribution data of chewing lice in the Maluku region.